2015
DOI: 10.1002/lno.10234
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemistry and microbial diversity in the marine cavity beneath the McMurdo Ice Shelf, Antarctica

Abstract: Ice shelves surround 75% of Antarctica's coastline and are highly sensitive to climate change; several have recently collapsed and others are predicted to in the near future. Marine waters beneath ice shelves harbor active ecosystems, while adjacent seas can be important areas of bottom water formation. Despite their oceanographic significance, logistical constraints have resulted in few opportunities to directly sample subice shelf cavities. Here, we present the first data on microbial diversity and biogeoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 86 publications
0
23
2
Order By: Relevance
“…The J9 sediment and water column studies showed microbial communities capable of metabolizing organic carbon substrates and fixing inorganic C in the dark (Horrigan, ), and a benthic community dominated by scavengers (Lipps et al, ). Data from closer to the ice shelf margin (Vick‐Majors, Achberger et al, ) revealed dark inorganic C‐fixation rates similar to those determined by Horrigan (; ~6 nmol C L −1 day −1 ) that were exceeded by heterotrophic microbial carbon demand. These results imply that in situ carbon production is insufficient to sustain the carbon demand under the RIS and that other sources of DOC are required.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…The J9 sediment and water column studies showed microbial communities capable of metabolizing organic carbon substrates and fixing inorganic C in the dark (Horrigan, ), and a benthic community dominated by scavengers (Lipps et al, ). Data from closer to the ice shelf margin (Vick‐Majors, Achberger et al, ) revealed dark inorganic C‐fixation rates similar to those determined by Horrigan (; ~6 nmol C L −1 day −1 ) that were exceeded by heterotrophic microbial carbon demand. These results imply that in situ carbon production is insufficient to sustain the carbon demand under the RIS and that other sources of DOC are required.…”
Section: Resultsmentioning
confidence: 64%
“…However, long residence times (~3.5 yr; Smethie & Jacobs, ) provide time for drawdown of supplemental DOC under the ice during water mass transport. Indeed, DOC concentrations in source waters beneath (Vick‐Majors, Achberger et al, ) or proximate to (Bercovici et al, ) the McMurdo Ice Shelf were approximately 40 μmol C L −1 (~37 μmol C L −1 , Vick‐Majors, Achberger et al, ; ~47 μmol C L −1 in Ross Sea Dense Shelf Water, Bercovici et al, ), while average DOC concentrations in water collected at the GZ were approximately twice these values (75 μmol C L −1 ). Apparent DOC enrichment at the GZ raises the possibility that subglacial outflows could be an important subsidy to coastal and estuarine biogeochemical processes under the RIS.…”
Section: Resultsmentioning
confidence: 99%
“…OTUs with high betweenness centrality values might possess high impact on other interactions in the community ( Greenblum et al, 2012 ). Keystone nodes in co-occurrence networks tend to have maximum betweenness centrality values ( Vick-Majors et al, 2015 ; Banerjee et al, 2016 ). Based on betweenness centrality, most keystone bacterial nodes in our study belonged to the most abundant phyla Proteobacteria and Bacteroidetes in both top- and subsoil.…”
Section: Discussionmentioning
confidence: 99%
“…After passing through the filtration and UV treatment system, the drilling fluid was heated to 90 • C and pressurized for drilling operations within the boiler units [49], which also served to 'flash pasteurize' the water. The effectiveness of the water treatment unit was verified in the USA prior to deployment and when mated to the hot water drill during a test that penetrated the McMurdo Ice Shelf [50]. Drilling fluid was initially generated by melting snow collected at the surface near the drill location, but upwind of airfield and power generation operations.…”
Section: Sampling Subglacial Lake Whillans (A) Clean Access Approachmentioning
confidence: 99%